Increasing the competitiveness of herbal beverage products garuda women farmer group, Cipayung Village, South Tangerang City through understanding of accounting and taxation digital based - Devid Putra Arda; Aep Saefullah; Ahmad Fadli; Fisy Amalia (Peneliti Teknologi Teknik Indonesia, 2023)
This Community Service activity captures the increase in the competitiveness of home industry herbal drink products. This activity is motivated by a strong desire to encourage women farmers who join the Garuda Women Farmers Group (KWT) in Cipayung Village, South Tangerang City to increase awareness and understanding of the importance of knowledge of accounting and taxation. as a pillar of business success . In the end , KWT is also one of the manufacturers of herbal drinks for health and fitness with a brand